The Socialization of Batik Culture to Enhance Children’s Creativity in a Puchong Guidance Studio In Kuala Lumpur, Malaysia - Hayatun Sabariah; Nurul Hasanah; Lia Ariska Ritonga; Istihara Safitri; Ratika Dewi (Sultan Publisher, 2025)
This socialization program for the introduction of batik culture in Sanggar Bimbingan (SB) Puchong, Kuala Lumpur, Malaysia, aims to provide insight into the art of batik and train the skills of Indonesian migrant workers (TKI) children in making simple batik works. This activity was carried out by students of the International Community Service Program (KKN) of the Jam'iyah Mahmudiyah Institute of Langkat using a participatory method involving the presentation of theory, demonstration of batik techniques, and hands-on practice. With a descriptive qualitative approach, data were collected through observation and direct interaction with participants totaling 35 children. The results of the activity showed that the SB Puchong children not only gained technical skills in batik making, but also increasingly understood the philosophy and cultural values contained in batik. The enthusiasm of the participants can be seen from their interest in choosing motifs, mixing colors, and applying both dip and colet dyeing techniques.In addition, the training increased the children’s appreciation of Indonesia’s cultural heritage and fostered a sense of pride in their cultural identity despite being in an overseas environment. The evaluation of the activity showed that the practice-based method was effective in improving the participants’ understanding and skills, as well as providing valuable experience in the creative process of making batik. With the success of this program, it is hoped that the children's awareness of the importance of cultural preservation and can continue to develop their batik skills in the future.